Igf-1 gene therapy as a potentially useful therapy for spontaneous prolactinomas in senile rats - Brown, Oscar Alfredo (2018)
Background: Insulin-like Growth Factor1 (IGF1) is a powerful neuroprotective molecule. We have previously shown that short-term hypothalamic IGF1 gene therapy restores tuberoinfundibu-lar dopaminergic neuron function in aging female rats. Objective: Our aim was to implement long-term IGF-I gene therapy in pituitary prolactinomas in senile female rats. Methods: Here, we assessed the long-term effect of IGF1 gene therapy in the hypothalamus of young (4 mo.) and aging (24 mo.) female rats carrying spontaneous pituitary prolactinomas. We constructed and injected a Helper-Dependent (HD) adenovector expressing the gene for rat IGF1 or the reporter red fluorescent protein DsRed. Ninety-one days post vector injection, all rats were sacrificed and their brains and pituitaries fixed. Serum prolactin (PRL), Estrogen (E2) and progesterone (P4), as well as hypothalamic IGF1 content, were measured by RIA. Anterior pituitaries were immunostained with an anti-rat PRL antibody and submitted to morphometric analysis. Results: DsRed expression in the Mediobasal Hypothalamus (MBH) was strong after the treatment in the DsRed group while IGF1 content in the MBH was higher in the IGF1 group. The IGF1 treatment affected neither pituitary weight nor PRL, E2 or P4 serum levels in the young rats. In the old rats, IGF1 gene therapy reduced gland weight as compared with intact counterparts and tended to reduce PRL levels as compared with intact counterparts. The treatment significantly rescued the phenotype of the lactotropic cell population in the senile adenomas. Conclusion: We conclude that long-term hypothalamic IGF1 gene therapy is effective to rescue spontaneous prolactinomas in aging female rats.